Respon Masyarakat Terhadap Manajemen Pengelolaan Madrasah Tsanawiyah Negeri Kedunggalar Kab. Ngawi Jawa Timur Tahun 2015 - Asror, Khozinatul, Dr. Sabar Narimo, M.M, M.Pd, Dr. Sudarno Shobron, M.Ag (2016)
Globalized world civilization made new lifestyle and other social changs which is happen in our surrounding society. In the changes and the new styles willy-nilly forces education, world especially Islamic education institutions (school) to give the change to ward the better in order that can equal the society development and able to fulfill society necessary. Most of the Islamic education has not been managed adequately and teachers professionalism is still very slow in generally. If that organization managed by management professional system, afford to understand and respons to the claim along with society aspiration, so the organization will get the bigger opportunity to be eminent choice and first for society. Focus in this research it is men how to manage the management of MTsN Kedunggalar and society response in Kedunggalar who prefer choose MTsN Kedunggalar as the place of their children education. As for the purpose in this research is for knowing the management of MTsN Kedunggalar Ngawi. This research is field research which is located in MTsN Kedunggalar Ngawi. The approachment in this research uses with participant observation technic and case studying plan. Accumulation of date technic is done by means of isceral interview participant observation of documentation studying. The election of research informant by purposif technic is fused with snow ball sampling. After accumulated data by means of all the technic afferword that is examined by date reduction way, data presentation and conclusion drawing. The point of this research is planning done by head. Master with PKM of MTsN Kedunggalar at freshmen year of lesson. Organizing is giving as assigment responsibility,and coordinating. Actuating is giving motivation and the act of growing of ruhul jihad to all of their subordinates and controlling as corrective action of all programs in school (madrasah). According to society response in Kedunggalar the headmaster is disciplined, be assertive, be able to give motivation and an inspiration for subordinates, student althought their parent for school progress. MTsN Kedunggalar Ngawi inspires parents' dream and hope, in other that their children have two competitions, namely IPTEK competition and religion spiritual (IMTAQ).